Does Regulatory Forfeiture of Fiduciary Assurance Undermine Justice? - Rina Arum Prastyanti; Nguyen Thi Thu Hang; Imiefoh Andrew Ikhayere (Contrarius, 2026)
This study examines fiduciary security by emphasising the legal consequences arising from the seizure of fiduciary objects upon the rights of creditors and debtors, and by comparing fiduciary regulatory frameworks in Indonesia, Australia, and the United States. The research adopts a normative legal method utilising secondary data in the form of primary and secondary legal materials. The approaches employed include statutory, conceptual, and comparative approaches to analyse the norms, principles, and practices governing fiduciary law across different jurisdictions. The research is descriptive and analytical, and it applies qualitative juridical analysis. The findings indicate that the seizure of fiduciary objects carries significant legal implications for both creditors and debtors, and that the implementation of Law Number 42 of 1999 concerning Fiduciary Security has not fully safeguarded the interests of all parties. The international comparison reveals the necessity for clearer mechanisms for the enforcement of fiduciary security and the protection of creditors’ rights. Accordingly, a reconstruction of the normative framework within the Fiduciary Security Law is required to realise Rawlsian justice, through the strengthening of legal protection, the certainty of enforcement, and the equitable balance of rights between creditors and debtors.